Research on a DC interconnection system based on a cascaded three-level converter for an island multi-energy microgrid - Liu, Xiaomin; Wang, Zheng; Liu, Shangke; Bai, Bin; Du, Xiangnan (Frontiers in Energy Research, 2024)
With the world's low-carbon energy transformation, Island microgrid is developing rapidly because it can achieve energy saving and carbon reduction. Island multi-energy microgrid includes photovoltaic, double-fed fan, battery energy storage system,and AC and DC loads.However, microgrids with a high proportion of renewable energy have problems such as large power supply fluctuations and poor power quality. If they are directly connected to AC power grid interconnection, the reliability and stability of the system will be greatly affected. In this paper, a Cascaded Neutral Point Clamped Three-level Converter(C-NPC) DC interconnection system scheme and control technology for island multi-energy microgrid are proposed to achieve reliable power supply, flexible multi-mode control and low-carbon stable operation of multi-energy microgrid on island or remote mountain area.Finally, taking an island interconnection project in the east coast of China as the research object, a typical system operation test is carried out to verify the good operation characteristics of the system.The research results of this paper can promote the overall utilization rate of clean energy in the island regional power grid, achieve carbon reduction, promote global carbon neutrality.The voltage source converter based high voltage dc (VSC-HVDC) transmission method for island interconnection does not require the synchronization of AC systems at both ends, and has several advantages, such as reducing the dependence of weak isolated network on standby capacity and At present, most of the island power generation systems mainly use diesel generators to meet the electricity demand of the island. This power supply mode has low energy utilization efficiency, and emits a lot of exhaust gas, causing great damage to the ecological structure and environment of the island region.